Continuous low dose inhaled nitric oxide for treatment of severe pulmonary hypertension after cardiac surgery in paediatric patients. Issue 1 (January 1995) - Beghetti, M.; Habre, W.; Friedli, B.; Berner, M.
Abstract : OBJECTIVE--To assess the effect of inhaled nitric oxide (NO) on severe postoperative pulmonary hypertension in children after surgical repair of a congenital heart defect. DESIGN--A pilot study of NO administration to 7 consecutive children who required adrenergic support and in whom postoperative mean pulmonary artery pressure was more than two thirds of mean systemic pressure and persisted despite alkalotic hyperventilation. SETTING--Routine care after cardiac surgery for congenital heart disease in a multidisciplinary paediatric intensive care unit. METHODS--Continuous inhalation of NO, initially at 15 ppm. Therefore, daily attempts at complete weaning or at reducing NO to the lowest effective dose. RESULTS--In 6 of the 7 children NO inhalation selectively decreased mean (SD) pulmonary artery pressure from 51 (12) to 31 (9) mm Hg (P < 0.05) while mean systemic arterial pressure was unchanged (68 (10) v 71 (7) mm Hg) (NS) and the arteriovenous difference in oxygen content decreased from 6.7 (0.9) to 4.8 (0.8) vol% (P < 0.05). Concomitantly PaO2 increased from 158 (98) to 231 (79) mm Hg) (P < 0.05). The seventh child showed no response to NO up to 80 ppm, could not be weaned from cardiopulmonary bypass, and died in the operating room. In responders, attempts at early weaning from NO inhalation always failed and NO at concentrations of less than 10 ppm was continuously administered for a median of 9.5 days (range 4 to 16 days) until complete weaning was possible from a mean dose of 3.9 (2.9) ppm. Methaemoglobinaemia remained below 2% and nitrogen dioxide concentrations usually ranged from 0.1 to 0.2 ppm. One child later died and five were discharged. A few months after surgery Doppler echocardiography (and catheterisation in one) showed evidence of regression of pulmonary hypertension in all 5. CONCLUSIONS--Inhalation of NO reduced pulmonary artery pressure in children with severe pulmonary hypertension after cardiac surgery and this effect was maintained over several days at concentrations carrying little risk of toxicity.